ANALYSIS OF SUBVENTIONS FOR AGRICULTURE IN REPUBLIC OF SERBIA AND REPUBLIC OF SRPSKA - Jović, Ljiljana; Kosanović, Nada; Vukadinović, Predrag (Economics of Agriculture, 2015)
In this paper, a comparative analysis of subventions for agriculture and rural development is conducted, based on the budgets of Republic of Serbia and Republic of Srpska. Based on the analysis of the gross value added and the subvention amount in the period 2008-2013, it is concluded that there is no country with the causativelyconsequent connection between the subvention volume and gross value added which ensigns to inadequate policy of stimulations. Besides that, it is noticed that there is no clear trend in the level of assets appropriation, as well as the structure of subvention benefciaries, which refers that the policy of agricultural stimulation and village in none of the countries has the label of long-term elaborated goals, but it is more the product of current movements in public revenues, i.e. short-term defned political-economic priorities.